"Apositía". Study of the Term from the "Corpus Hippocraticum" to Galeno - López Férez, Juan Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
This paper studies the word apositía from the Corpus Hippocraticum up to Galen.